Code-switching on Facebook in Denmark and Lithuania - Jakelienė, Eglė (Taikomoji kalbotyra, 2018)
This paper examines and compares Danes’ and Lithuanians’ code-switching on Facebook. Currently Facebook is one of the most popular social media platforms, where a lot of human communication occurs. The language on such platforms is similar to spoken language in its informality, yet it is written and is therefore at least somewhat planned. This research was carried out by collecting status updates and their respective comments from Facebook profiles of six well-known people (three people from each country) and their followers. Based on the quantitative and qualitative analyses, it seems that the way Lithuanians and Danes switch codes is mostly universal and used to achieve similar purposes. The most common foreign language for code-switching in each dataset was English. Both Danes and Lithuanians switched between their respective native and foreign languages in order to mark discourse, emphasize a point, attract reader’s attention, show identity and refer to a different context. However, while code-switching between the native language and English was used for all these purposes, other languages were chiefly used to refer to different cultural contexts. In the future, more research on how Lithuanians code-switch on Facebook could be carried out, possibly focusing on smaller groups of people, and thus being able to make ethnographic observations.